Ovarian effects of vitamin D: a systematic review - G. E. Chernukha; O. V. Yakushevskaya (Медицинский совет, 2021)
The history of the discovery of vitamin D (VD) has crossed 100 years. Initially, VD deficiency was limitedly associated with the development of rickets in children. Later, on the basis of a number of studies, it was found that VD deficiency is a risk factor for osteoporosis in men and women. However, the traditional concept of VD as the main regulator of calcium-phosphorus metabolism has undergone dramatic changes over the past two decades. A prerequisite for revising the role of VD and the spectrum of its biological properties was the identification of the distribution of its specific receptors in the body. VD receptors are expressed in the intestine, thyroid and parathyroid glands, kidneys, ovaries, uterus, placenta, hypothalamus, pituitary gland and play a vital function not only in calcium homeostasis. Accordingly, the list of target organs for VD action has been modified. VD deficiency, calculated on a pandemic scale, is a factor that increases the risk of developing not only osteoporosis, but also a number of other diseases. Observational and epidemiological studies have shown that reproductive system disorders are very often combined with VD insufficiency / deficiency. Subsequent scientific research aimed at establishing the role of VD in the formation of a particular pathology of the reproductive system has shown very ambiguous results. VD is recognized as an essential component of maintaining a woman’s reproductive health. Of course, the presence of an established association is not evidence of a causal relationship. There is a need for additional testing. This review focuses on the effect of VD on ovarian function and the formation of various dysfunctional conditions.